Vaginismus in Primary Health Care: Challenges in Diagnosis and Management - A Narrative Review - Riza Fitria (Riviera Publishing, 2025)
Vaginismus is a female sexual dysfunction characterized by involuntary spasms of the pelvic floor muscles that impede vaginal penetration, affecting 5-7% of women worldwide with higher prevalence reported in Eastern countries. This condition not only causes physical pain but also impacts mental health and interpersonal relationships. This article aims to explore the diagnostic challenges of vaginismus in primary health care settings and present evidence-based management strategies to support clinicians in delivering effective, patient-centered care. A narrative review was conducted by analyzing national and international literature published between 2019-2025 through PubMed, Google Scholar, and ScienceDirect databases using keywords vaginismus, primary care, diagnosis, and management. The main challenges in diagnosing vaginismus in primary care include overlapping symptoms with other conditions, limited consultation time, stigma surrounding sexual health, and insufficient competence among healthcare providers. The DSM-5 has merged vaginismus and dyspareunia into Genito-Pelvic Pain/Penetration Disorder (GPPPD) to facilitate classification. Management is multimodal involving education, pelvic floor muscle physiotherapy, psychological counseling, and simple pharmacotherapy. Primary health care plays an important role as the main gateway for vaginismus management. An integrated approach including proactive screening, empathetic gradual examination, initial therapy, and timely referrals can improve patient quality of life and success of subsequent therapy.